ANALISIS PENGARUH RASIO KEUANGAN RENTABILITAS TERHADAP PENDAPATAN MARGIN MURABAHAH BANK SYARIAH (Studi Kasus pada PT. Bank Mega Syariah Periode 2005-2012) - Achmad Nurdany (Khazanah: Jurnal Mahasiswa, 2013)
This research is aimed to examine the affect of financial profitability ratios to ward murabahah margin revenue especially in PT. Bank Mega Syariah during 2005-2012. Financial profitability ratios consist of Return On Asset (ROA), Return On Equity (ROE), Net Core Operational Margin (NCOM), and Operational Efficiency Ratio (OER). The data analysis technique uses multiple linier regression with the method of Ordinary Least Square (OLS). The hipothesys testing in this research uses t test for individual parameter and F-test for collective parameter with the significance level 5%. In addition, to meet the assumptions of OLS in performing multiple linear regression, also included normality test, autocorrelation test, heteroskedasticity test, and multikolinearity test. The results show that simultanously, financial profitability ratio significantly affect the murabahah margin revenue, but individually the Operational Efficiency Ratio (OER) does not make any affection. Overall, the regression model is good enough, because the predictive ability of financial profitability ratios toward murabahah margin revenue is 70%, and 30% are affected by some factors that are not included in this model of research.